Teacher-Reported Priorities and Practices for Students With Autism: Characterizing the Research-to-Practice Gap. (June 2020) - Brock, Matthew E.; Dynia, Jaclyn M.; Dueker, Scott A.; Barczak, Mary A.
Despite broad consensus that a research-to-practice gap exists in the education of students with autism, the extent of this gap has not been well studied. We surveyed 99 teachers in Ohio about their highest priority goals for students with autism spectrum disorder (ASD), their approach for addressing these goals, the degree to which students had made progress, and barriers to student progress. Only half of all teachers described an approach that included any evidence-based practice (EBP). Teachers often reported inadequate progress on Individualized Education Program (IEP) goals, and that identifying and implementing effective intervention practices were barriers to progress. We found some alignment between the outcomes prioritized by teachers and those measured by researchers in the literature, although teachers more highly prioritized academic and cognitive outcomes.